Application of PBL Model on Design Preparation Competencies With a Critical Thinking Approach - Aninda, Catleya Azka; Bidari, Citra Laksmi; Safira, Karina Beauty; Putri, Ni Nengah Cindy Swandewi; Yuliana, Qoriah Setia; Lutfiati, Dewi; Cahyani7, Wahyu Dwi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study was conducted to analyze the application of PBL model that influences students' learning outcomes and critical thinking skills in the subject of design prerequisites. The method used is Classroom Action Research (CAR) with three cycles with a sample of 31 students of class XI KC 3 SMKN 6 Surabaya. The results of the study showed a significant increase in the cognitive aspect and critical thinking skills of students. The completion of learning the cognitive aspect using the N-Gain test analysis resulted in an increase from the percentage of cycle 1 33%, cycle 2 57% and finally cycle 3 78% effectively. Students' critical thinking skills also increased in each cycle, namely cycle 1 (88%), cycle 2 (92%) and cycle 3 (97%). Therefore, the application of the PBL model can significantly improve students' critical thinking skills in design prerequisite competencies.